DEVELOPMENT OF AN ELECTROCHEMICAL SENSOR MODIFIED WITH MWCNT-COOH AND MIP FOR DETECTION OF DIURON - Wong, Ademar [UNESP]; Foguel, Marcos Vinicius [UNESP]; Khan, Sabir [UNESP]; Oliveira, Fernanda Midori De; Tarley, César Ricardo Teixeira; Sotomayor, Maria D.P.T. [UNESP] (Elsevier, 2015)
An electrochemical sensor modified with a molecularly imprinted polymer (MIP) and carboxyl-functionalized multi-walled carbon nanotubes (MWCNT-COOH) was developed for the sensitive and selective detection of diuron in river water samples. An MIP was obtained by bulk polymerization using the best monomer (methacrylic acid) selected by computational simulation. The surface characteristics of the MIP and NIP (control polymer) samples were evaluated by means of surface area and pore volume determinations, using the BET method. The adsorption efficiency of the MIP was determined in adsorption tests that revealed high adsorption, relative to the control polymer. In addition, MWCNTs functionalized with carboxyl groups were used to enhance the performance of the sensor. Electrochemical studies of diuron using the MIP and MWCNT-COOH immobilized on a carbon paste electrode were performed with wave square voltammetry (SWV). The analytical parameters pH, buffer composition, and amounts of MWCNT-COOH and MIP were investigated and optimized. Excellent results were obtained with a linear range of between 5.2 × 10-8 and 1.25 × 10-6 mol L-1, detection limit of 9.0 × 10-9 mol L-1, and sensitivity of 5.1 × 105 μA L mol-1. The MWCNT-COOH-MIP/CPE showed an enhanced electrochemical response, with sensitivity 7.9-fold greater than for a plain carbon paste electrode (CPE). Application of the sensor using river water samples resulted in recoveries between 96.1 and 99.5% and RSD <5% (n=3), demonstrating the reliability of this device.
Keywords: adsorption; Diuron; electrochemical sensor; molecularly imprinted polymer; MWCNT-COOH